The Implementation of Japanese Animation (Anime) In Advertising - Aziz, Munafsin; Ong, Susy (Jurnal Indonesia Sosial Sains, 2023)
Anime has become a popular culture phenomenon in Japan and around the world. The use of anime in advertisements has become one of the most effective marketing strategies in Japan. This article discusses the use of anime in advertisements in Japan, as well as the advantages of using anime in advertisements. This article explains the popularity of anime in Japan and how it has become a part of the country's consumer culture. Then, this article also discusses how anime is used in advertising to attract consumer attention and increase product sales. Furthermore, this article discusses the advantages of using anime in advertisements, including being effective in reaching a young market, increasing brand appeal, and giving a more attractive and unique impression to the advertised product. In this article, it is also explained that the use of anime in advertising can also increase consumer engagement and build an emotional connection between brands and consumers. Apart from that, this article also contains examples of advertisements using anime, both in the private and government sectors. Anime can also help brands create positive and imaginative images that can enhance brand impressions. Overall, the use of anime in advertising in Japan has many advantages and is an effective marketing strategy.